2015
DOI: 10.3390/md13106117
|View full text |Cite
|
Sign up to set email alerts
|

Redox Status and Neuro Inflammation Indexes in Cerebellum and Motor Cortex of Wistar Rats Supplemented with Natural Sources of Omega-3 Fatty Acids and Astaxanthin: Fish Oil, Krill Oil, and Algal Biomass

Abstract: Health authorities worldwide have consistently recommended the regular consumption of marine fishes and seafood to preserve memory, sustain cognitive functions, and prevent neurodegenerative processes in humans. Shrimp, crabs, lobster, and salmon are of particular interest in the human diet due to their substantial provision of omega-3 fatty acids (n-3/PUFAs) and the antioxidant carotenoid astaxanthin (ASTA). However, the optimal ratio between these nutraceuticals in natural sources is apparently the key facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Several reports suggested that the efficiency of H. pluvialis extract in protecting the inflammation in brain cells is attributed to the antioxidant carotenoid ASTA which is existed in H. pluvialis [46]. In the same line, it has been found that ASTA promoted anti-inflammatory effect by inhibiting the mitochondrial β-oxidation and suppressing the free radicals generation [47].…”
Section: Effect Of H Pluvialis Extract On the Cytokines Levelmentioning
confidence: 48%
“…Several reports suggested that the efficiency of H. pluvialis extract in protecting the inflammation in brain cells is attributed to the antioxidant carotenoid ASTA which is existed in H. pluvialis [46]. In the same line, it has been found that ASTA promoted anti-inflammatory effect by inhibiting the mitochondrial β-oxidation and suppressing the free radicals generation [47].…”
Section: Effect Of H Pluvialis Extract On the Cytokines Levelmentioning
confidence: 48%
“…Also, astrocytes can decrease the toxic effect of the abnormal increase in glutamate release induced by corticosteroids at the presynaptic level, by uptaking the glutamate from the synaptic space. On the other hand, KO components such as omega-3 and astaxanthin can prevent oxidative stress and diminish the deleterious effects of stress and Neuroinflammation on brain function (Barros et al, 2014; Polotow et al, 2015; Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…The International Society for the Study of Fatty Acids and Lipids recommends 500 mg of EPA and DHA for the general adult population (70 kg). Based on the report, 7 mg of EPA and DHA per kilogram of body weight (BW) was normalized for experimental rats . Fish oil was used as a positive control for this study (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the report, 7 mg of EPA and DHA per kilogram of body weight (BW) was normalized for experimental rats. 24 Fish oil was used as a positive control for this study (Table S1). The experimental animals were divided into three groups as follows: (i) Control: No EPA and DHA; (ii) microalga group: 5.7 mg of EPA and 1.4 of DHA, which equals 7.1 mg of EPA + DHA per kg BW; (iii) fish oil group: 4.2 mg of EPA and 2.9 mg of DHA, which equals 7.1 mg of EPA + DHA per kg BW.…”
Section: Supplementsmentioning
confidence: 99%